Indizi di sviluppi romanzi riflessi nelle voci germaniche e nei nomi propri - NICOLETTA FRANCOVICH ONESTI (Filologia Germanica)
As the title of a 2007 Magdeburg conference goes (Namen des Frühmittelalters als sprachliche Zeugnisse und als Geschichtsquellen), onomastics can be a special type of historical source, as well as an early witness of linguistic developments, especially for the early medieval centuries, when Romance languages were not yet recorded in written documents. Onomastics and Germanic words occurring in Italian written sources can therefore reflect early Romance phonetic developments that would not otherwise show at such early dates. This paper tries to collect all evidence from names and from Germanic words (Gothic Ghiveric, Lombard Arnucciolu, ischerpa, isnaidas etc.) that may reflect early Romance tendencies in a Latin context. Among them, in Tuscany as early as the 8th century we find traces of a local [ž] sound, developed from the corresponding voiceless consonant, the new Italian preposition da ‘from’ occurring before proper names, and also the new Romance suffixes occurring in anthroponyms. In general we can also grasp the beginnings of dialect characteristics, from northern Italian to Tuscan and to southern dialects.